I2-catalyzed three-component synthesis of 3-selenylated pyrazolo[1,5-a]pyrimidines - Choudhuri, Tathagata; Paul, Suvam; Sikdar, Papiya; Das, Sourav; Sawant, Sanghapal D.; Bagdi, Avik Kumar (New Journal of Chemistry, 2024)
A straightforward protocol has been developed to access 3-selenylated pyrazolo[1,5-a]pyrimidines from readily available amino pyrazoles, chalcones, and diaryl/dialkyl diselenides. This I-2-catalyzed methodology is highly useful for synthesizing a wide range of functionalized 3-(aryl/alkylselanyl)pyrazolo[1,5-a]pyrimidine derivatives. Mechanistic investigation disclosed that iodine catalysis is very important in both the cyclization process as well as in the C-H selenylation step. Moreover, the developed reaction conditions are also applicable for the cyclization of amino pyrazole with enaminone followed by C-H selenylation in one pot. The use of simple reagents and catalyst, wide substrate scope, mild and metal-free reaction conditions, and practical applicability are the attractive facets of this approach.